Model Pengajaran Berbasis Penugasan Dalam Meningkatkan Prestasi Belajar PPKn Pada Siswa Kelas XI Semester 1 Kompetensi Keahlian Tata Busana SMKN 1 Kalitengah Tahun Pelajaran 2019-2020 - Yamtur Kamun, Lik (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2020)
The purpose of this study is to: (a) To find out the improvement of PPKn learning achievement after the implementation of Assignment-based contextual learning in class XI students in semester 1 of the competence of Fashion Design at SMKN 1 Kalitengah for the 2019-2020 academic year. (b.) Affecting the contextual learning of the Assignment-based teaching model in improving Civics learning achievement in class XI Semester 1 students of the Fashion Design skill competency of SMKN 1 Kalitengah for the 2019-2020 academic year. This study uses three rounds of action research. Each round consists of 4 stages, namely: planning, observation and observation, reflection and revision. The target of this research is the students of class XI Semester 1 Competency of Fashion Design at SMKN1 Kalitengah for the 2019-2020 academic year. The data obtained in the form of test results, observation sheets of teaching and learning activities. From the results of the analysis it was found that student learning achievement has increased from cycle I and cycle II, namely, cycle I (73.33%), and cycle II (90.00%). are (a) There is an increase in PPKn learning achievement after the implementation of contextual learning of the Assignment-based teaching model in class XI Semester 1 students of the Fashion Design Expertise Competence at SMKN 1 Kalitengah for the 2019-2020 academic year. (b.) There is an effect of contextual learning on the Assignment-based teaching model in improving Civics learning achievement in class XI Semesster 1 Competency of Dressing Skills at SMKN 1 Kalitengah for the 2019-2020 academic year.